Pengaruh Pembelajaran Berbasis Gamifikasi terhadap Motivasi Belajar Matematika Pasca Pandemi Covid-19 - Irnawati, Dionisia Retno; Makmur, Amelia; Istiyowati , Lucia Sri (Jayapangus Press, 2024)
One of the trends that has gotten stronger after the Covid-19 Pandemic is the habit of students using gadgets to study, surf, play and spend their time. This habit influences the motivation and learning outcomes in school. Consequently, conducting research is needed to utilize digital game applications as part of gamification-based learning media. This is important to increase the learning interest of students who like digital games. This study aims to determine the effectiveness of using gamification-based learning methods in increasing student motivation. The research method used was a survey using questionnaires for junior high school students. Statistical analysis was conducted to determine differences in learning motivation before and after the implementation of gamification in mathematics class. The results of the analysis show that the implementation of gamification in mathematics can increase student motivation by 13.03% compared to conventional learning. From the several question items, it can be seen that gamification made learning mathematics more fun (3.65) and 97.45% of students said that their learning concentration was better with the implementation of gamification in the mathematics class. Looking at the average results of the questionnaire after gamification-based learning at class VII and IX levels there is no significant difference, both show high averages showing that at different levels students are equally interested in gamification-based learning. Thus it can be concluded that the implementation of gamification in mathematics learning has a significant influence on increasing student learning motivation.